Drug repurposing in cancer. (October 2017) - Sleire, Linda; Førde-Tislevoll, Hilde Elisabeth; Netland, Inger Anne; Leiss, Lina; Skeie, Bente Sandvei; Enger, Per Øyvind
Graphical abstract: Abstract: Cancer is a major health issue worldwide, and the global burden of cancer is expected to increase in the coming years. Whereas the limited success with current therapies has driven huge investments into drug development, the average number of FDA approvals per year has declined since the 1990s. This unmet need for more effective anti-cancer drugs has sparked a growing interest for drug repurposing, i.e. using drugs already approved for other indications to treat cancer. As such, data both from pre-clinical experiments, clinical trials and observational studies have demonstrated anti-tumor efficacy for compounds within a wide range of drug classes other than cancer. Whereas some of them induce cancer cell death or suppress various aspects of cancer cell behavior in established tumors, others may prevent cancer development. Here, we provide an overview of promising candidates for drug repurposing in cancer, as well as studies describing the biological mechanisms underlying their anti-neoplastic effects.